2020
DOI: 10.3390/ijms21197348
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Inhibits NF-κB-Dependent CCL5 Transcription by Targeting IκB Kinase in the Atopic Dermatitis-Like Inflammatory Microenvironment

Abstract: Chrysin (5,7-dihydroxyflavone) is a natural polyphenolic compound that induces an anti-inflammatory response. In this study, we investigated the molecular mechanism underlying the chrysin-induced suppression of C-C motif chemokine ligand 5 (CCL5) gene expression in atopic dermatitis (AD)-like inflammatory microenvironment. We showed that chrysin inhibited CCL5 expression at the transcriptional level through the suppression of nuclear factor kappa B (NF-κB) in the inflammatory environment. Chrysin could bind to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…Previous studies have shown that chrysin alleviates AD-like skin lesions in a mouse model [ 37 ] and reverses the NF-κB-mediated inhibition of C-C motif chemokine ligand (CCL) 5 [ 39 ]. TSLP plays a key role in AD progression, and TSLP upregulation is considered a hallmark of AD pathogenesis [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that chrysin alleviates AD-like skin lesions in a mouse model [ 37 ] and reverses the NF-κB-mediated inhibition of C-C motif chemokine ligand (CCL) 5 [ 39 ]. TSLP plays a key role in AD progression, and TSLP upregulation is considered a hallmark of AD pathogenesis [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chrysin has a pharmacological property that helps alleviate the clinical symptoms of AD by inhibiting the secretion of pro-inflammatory cytokines and chemokines [ 37 , 38 , 39 ]. TNFα is a major pro-inflammatory cytokine that is released from various immune cells and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations